Economic Growth and Circular Economy in the European Union: Novel Empirical Synergy Analyses Between Key Variables of Circular Economy and Gross Domestic Growth (GDP) and Gross National Income (GNI) - Kaivo-oja Jari; Vehmas Jarmo; Luukkanen Jyrki (Canada, 2025)
Sustainable development has been at the heart of European sustainability policy for a long time, firmly anchored in the European Treaties. The 2030 Agenda for Sustainable Development and its 17 Sustainable Development Goals (SDGs), adopted by the UN General Assembly in 2015, have given a new impetus to global efforts to achieve sustainable development. One key challenge of sustainable development policy is the smart orchestration of the circular economy in relation of economic growth processes. In our current economy, we take materials from the Earth, make products from them, and eventually throw them away as waste – the process is very linear. The linear operating model is also short-term. In a circular economy, by contrast, we stop waste being produced in the first place. We can re-plan, re-use and re-cycle. We may note that it is not possible to reach a sustainable growth process without well-functioning material recycling systems and functions of the circular economy. The well-functioning circular economy is good for business, people and the environment. The circular economy is a systems solution framework that tackles global challenges like climate change, biodiversity loss, waste, and pollution. There are needs and questions to transform every element of our take-make-waste system: (1) how we manage resources, (2) how we make and use products, and (3) what we do with the materials afterwards and (4) how we make trade with recycled materials. Only then when answer to these questions, can we create a thriving circular economy that can benefit everyone within the limits of our planet. Eliminating waste and pollution, circulating materials and products and regenerating nature are key functions of the circular economy. We must admit that waste is a human invention. If we move to a regenerative sustainability model, we begin to emulate natural systems. There is no waste in nature. This is a new invention of the circular economy. We have seen a lot of discussions about the circular economy, but less attention has been paid to the critical links between the circular economy and economic growth. The study provides an empirical contribution to this research gap. This empirical research can open up new insights and avenues into the development of sustainability science. If policymakers are not aware of the links between the circular economy and economic growth, it will seriously hamper the development of the circular economy in the world. In this sense, research in the field of circular economy is very important and it should be promoted in the world. The conference paper has a strong focus on the circular economy and changing dynamics of economic growth with key variables of the circular economy (CE). This comprehensive and empirical EU study elaborates following key variables of the circular economy: (1) Material footprint [CEI_PC020], (2) Resource productivity [CEI_PC030], (3) Generation of municipal waste per capita [CEI_PC031], (4) Generation of packaging waste per capita [CEI_PC040], (5) Recycling rate of municipal waste [CEI_WM011], (6) Recycling rate of e-waste [CEI_WM050], (7) Recycling of biowaste [CEI_WM030], (8) Trade in recyclable raw materials, Imports extra-EU27 (from 2020) [CEI_SRM020], (9) Exports extra-EU27 (from 2020) [CEI_SRM020], (10) Private investments, jobs and gross value added related to circular economy sectors [cei_cie010] and (11) Patents related to recycling and secondary raw materials [cei_cie020]. These 11 key CE variables are analyzed with synergy analysis method in relation to two key indicators of economic growth, Gross Domestic Product (GDP) and Gross National Income (GNI). The study is based on synergy analysis method, which reveals both positive and negative synergies of key variables, and also growth processes without any synergy. The analysis provides additional strategic information for decision-makers concerning SDGs in the long-run. Presenting regular monitoring tool of progress towards the SDGs in the EU context is essential for this conference paper. The method can be applied also in other global sustainability assessments. The data of study is collected from the Eurostat Circular Economy databases and data set covers years 2000-2020. The indicators of economic growth are from the World Bank Key Indicator database. This 20 years database provides a reliable empirical foundation to analyze interlinkages between economic growth and key variables of the circular economy. The conference paper reports various interesting empirical findings about the circular economy logic in the European Union. One key finding is that in the European Union the synergy levels between GDP and GNI indicator variables and the key variables of the circular economy are not at the same positive or negative levels, but may differ significantly from each other. This is an interesting finding for the management of economic growth policy in the European Union.
Papers presented in the 16th International Conference on Sustainable Development at the United Nations Economic and Social Commission for Asia and the Pacific (UNESCAP) Bangkok, Thailand, 2022